The meaning and end of religion - Smith, Wilfred Cantwell, 1916-2000 (Fortress Press, 1991)
Wilfred Cantwell Smith, maintained in this vastly important work that Westerners have misperceived religious life by making "religion" into one thing. He shows the inadequacy of "religion" to capture the living, endlessly variable ways and traditions in which religious faith presents itself in the world.
Keywords: Religion.; Religions.; Religion -- Historiography.; Faith.; Religion -- Historiographie.; Foi.; religion (discipline); religions (belief systems, cultures); faith.; Faith; Religion; Religion -- Historiography; Religions